Psychological strength among university students from the families of the martyrs in Wasit Governorate - Nasir Khalifa, Rashid; Sabeeh Abid, Siaq (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to find out the level of acceptance of mental toughness among university students who are families of political martyrs in Wasit governorate according to the gender variable. Well, to be entitled results from HDQ Search The researchers built a measure of psychological rigidity, and researchers used the interview as a tool to ensure the validity and reliability of paragraphs of res J of Q and had the interview outclass CAR researchers Foundation with political martyrs in Wasit province and met the sample asking permission of them to take photographs to be attached within supplementary research. In order to treat data statistically to achieve the goal of the research, the researchers used the following statistical methods: 1. Pearson correlation coefficient. 2- The T-test test-retest, It was extracted descriptive statistical indicators to measure and achieve researchers to the following: The individuals of the current research sample possess a level of psychological toughness higher than the hypothetical average for the scale.